Plate-girder railway bridges - Fitzmaurice, Maurice, 1861- (E. & F.N. Spon, 1895)
The great majority of bridges on a line of railway are short-span plate-girder bridges. This book is intended to help those young engineers who, joining an engineers office for the first time, find themselves engaged in this class of work.
Includes index.
Keywords: Plate girder bridges -- Design and construction.; Railroad bridges -- Design and construction.; elektronické knihy; electronic books